Myeloid cell plasticity in the evolution of central nervous system autoimmunity. Issue 1 (14th January 2018) - Giles, David A.; Washnock‐Schmid, Jesse M.; Duncker, Patrick C.; Dahlawi, Somiah; Ponath, Gerald; Pitt, David; Segal, Benjamin M.
Abstract : Objective: Myeloid cells, including macrophages and dendritic cells, are a prominent component of central nervous system (CNS) infiltrates during multiple sclerosis (MS) and the animal model experimental autoimmune encephalomyelitis (EAE). Although myeloid cells are generally thought to be proinflammatory, alternatively polarized subsets can serve noninflammatory and/or reparative functions. Here we investigate the heterogeneity and biological properties of myeloid cells during central nervous system autoimmunity. Methods: Myeloid cell phenotypes in chronic active MS lesions were analyzed by immunohistochemistry. In addition, immune cells were isolated from the CNS during exacerbations and remissions of EAE and characterized by flow cytometric, genetic, and functional assays. Results: Myeloid cells expressing inducible nitric oxide synthase (iNOS), indicative of a proinflammatory phenotype, were detected in the actively demyelinating rim of chronic active MS lesions, whereas macrophages expressing mannose receptor (CD206), a marker of alternatively polarized human myeloid cells, were enriched in the quiescent lesion core. During EAE, CNS‐infiltrating myeloid cells, as well as microglia, shifted from expression of proinflammatory markers to expression of noninflammatory markers immediately prior to clinical remissions. Murine CNS myeloid cells expressing the alternative lineage marker arginase‐1 (Arg1) were partially derived from iNOS + precursors and were deficient in activating encephalitogenic T cells compared with their Arg1 − counterparts. Interpretation: These observations demonstrate the heterogeneity of CNS myeloid cells, their evolution during the course of autoimmune demyelinating disease, and their plasticity on the single cell level. Future therapeutic strategies for disease modification in individuals with MS may be focused on accelerating the transition of CNS myeloid cells from a proinflammatory to a noninflammatory phenotype. Ann Neurol 2018;83:131–141